Ovalbumin-chitosan complex coacervation: Phase behavior, thermodynamic and rheological properties. (December 2016) - Xiong, Wenfei; Ren, Cong; Jin, Weiping; Tian, Jin; Wang, Yuntao; Shah, Bakht Ramin; Li, Jin; Li, Bin
Abstract: This paper investigated the influence of pH, ionic strength, and the ratio of protein/polysaccharide on the interaction between ovalbumin (OVA) and chitosan (CS) through turbidity, zeta potential, confocal laser scanning microscope (CLSM) and isothermal titration calorimetry (ITC). Dynamic rheometer was used to study rheological properties of the complex coacervates. Results of phase diagram and microstructure showed that complexes and coacervates were formed at specific pH values via the electrostatic interactions. The lower level of ionic strength ( C NaCl ≤200 mM) promoted the formation of OVA/CS coacervates, while higher ionic strength ( C NaCl >200 mM) inhibited the formation of coacervates due to the screening of macromolecular charges by salt ions. Additionally, the increase of OVA/CS ratio from 1:1 to 10:1 caused the decrease of critical pH (pHc and pHφ ). The interaction between OVA and CS was spontaneous exothermic process at pH 4.0 and pH 5.5 according to ITC measurement. The affinity constant and stoichiometric ratio between OVA and CS at pH 5.5 was much higher than that of pH 4.0. It indicated that the change of binding energy along with OVA titration depended on the pH. Moreover, dynamic rheological analysis results showed that the lower salt concentration ( C NaCl ≤50 mM) and OVA/CS ratio (from 1:1 to 3:1) promoted the formation of coacervates structure, which had a stronger gel strength. However, the higher salts and OVA/CS ratio (from 3:1 to 10:1) ( C NaCl >50 mM) led to weaker elasticity of OVA/CS coacervates. Graphical abstract: Highlights: OVA and CS could form complex coacervates depending on the solution pH. Ionic strength and protein/polysaccharide ratio are very important during the form of complex coacervates. In salt free condition, the affinity constant (K) and stoichiometric ratio between OVA and CS at pH5.5 is much higher than at pH4.0. When C NaCl ≤50 mM, the salt-enhanced effect favored the formation of the coacervate structure, exhibiting a stronger gel strength. Increasing the ratio of OVA/CS from 1:1 to 3:1 caused a stronger elasticity.